Evaluation of the Antidote Activity of Nimbu swarasa (Citrus limon Linn.) on Jayapala Seed (Croton tiglium Linn.) Induced Toxicity in Wistar Albino Rats - Mouneshwari; Mundugaru, Ravi; Kodavoor, Shobha Bhat (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Seeds of Jayapala (Croton tiglium Linn.) is a toxic compound which is commonly used in several Ayurvedic formulations following proper detoxification methods as mentioned in the Ayurvedic classics. Adarsha nigantu, one of the treatises of Ayurveda explains Nimbu swarasa (Lemon juice) as an antidote for Jayapala. The present study was aimed to determine the antidote activity of Nimbu swarasa (Citrus limon linn.) on Jayapala (Croton tiglium Linn.) seed induced toxicity on Wistar albino rats. Materials and Methods: A sub acute toxicity study was conducted on Wistar rats following the repeated dose 28 day oral toxicity study in rodents, 407 OECD guidelines which included administration of Jayapala seeds alone in one group and Jayapal seeds along with Nimbu swarasa in different doses in the other groups. Different haematological and biochemical parameters along with histopathology of important organs were carried out to access the antidote effect of Nimbu swarasa. Observation and Results: The repeated administration of Jayapala seed powder caused significant elevation in the serum liver enzymes like SGOT and SGPT (*P<0.5) and marked rise in the serum creatinine level. The co-administration of antidote Nimbu swarasa significantly attenuated Jayapala seed induced increase in the liver enzymes and reduced serum creatinine level. Histopathological examination of colon and jejunum revealed moderate epithelial cell erosions in Jayapala seeds administered group, whereas Nimbu swarasa caused mild to moderate protection in a dose dependant manner. Sections of spleen showed remarkable increase in the proportion of white pulp in toxicant group, whereas the Nimbu swarasa at higher dose level showed marked decrease in the white pulp proportion. The hepatic sections of toxicant group displayed mild cell infiltration and fatty changes in the hepatocyte with mild diffused necrosis whereas the sections of co-administration of antidotes showed normal cytoarchitecture. Conclusion: All the above findings are suggestive of Nimbu swarasa being an effective antidote against Jayapala induced toxicity.
Keywords: Antidote; Jayapala seeds; Nimbu swarasa; Haematological parameters; Histopathological examination; Toxicity